Social Developments Of Mughal India With Special Reference To Mobility Problems: A Historical Evaluation (Journal of Namibian Studies : History Politics Culture, 2023)
The major changes in Mughal India was migration. These moves were organised to take advantage of more plentiful employment opportunities. The immigrants to India brought their families and their traditions with them. Iranian and Turani immigrants settled in various parts of the Mughal Empire after coming to India. Their manner of life, social customs, and values were influenced by Indian society's traditions and customs. They made a substantial contribution to the growth of Indo-Mughal civilization and were absorbed into Indian culture. They significantly influenced the architecture, music, literature, painting, and other arts of Mughal India.  In this article, social developments of Mughal India with special reference to mobility problems has been discussed.